Disability Rights Violation: Failure to Provide Reasonable Accommodation and Employment Discrimination Against the Colorblind in Indonesia - Ni Putu Ayu Meylan Ardini; Made Wiswani Wacika; Kadek Agus Sudiarawan; Salwa Putri Hardiyan (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2026)
The fundamental right to work in Indonesia is paradoxically undermined by pervasive no color blindness recruitments, often enforced via the Ishihara test. While this practice appears neutral, it constitutes indirect discrimination by disproportionately excluding competent individuals with partial colour blindness without any objective justification. This study aims to analyse the validity of the Ishihara test, arguing that it is a discriminatory tool that violates human rights. Using normative legal analysis and empirical case studies, the findings show that partial colour blindness is primarily a sensory limitation which rarely affects functional capabilities in most professions. Field data reveals a widespread misconception among employers that equates partial colour blindness with an inability to recognise hazards. Furthermore, many institutions enforce colour vision standards as an administrative hurdle without conducting job analyses relevant to the actual requirements of the role. The research concludes that the Ishihara test is widely misused as a definitive pass/fail determinant. This practice contravenes Law No. 13/2003 on Manpower regarding equal opportunity, and Law No. 8/2016 on Persons with Disabilities, which mandates the fulfilment of employment rights and reasonable adjustments. Automatic rejection without interactive dialogue constitutes a direct breach of legal obligations. This research advocates for an inclusive, fair, and dignified employment ecosystem in Indonesia.